The Relationship Between The Explosion Of Arm Muscles And Balance With Bullet Rejection Of Ortodok's Style - Mikkey Anggara Suganda; Riyan Jaya Sumantri (Universitas Negeri Semarang, 2022)
This study is to ascertain the relationship between arm muscle explosive power and balance. At SMK Negeri 1 Cirebon, students had a sample size of 30 participants. The influence of arm muscle explosive power tests using two-handed medicine ball throws, balance tests utilizing stork stands, and orthodox style shot put tests are the data that were collected. Through analysis of the correlation between arm muscle explosive power and conservative style shot put using the product moment formula calculation, it was determined that the correlation between arm muscle explosive power and balance had a moderate relationship. The value of count was 0.437 > rtable 0.374 and the origin there will be a significant test, and it turns out that count is greater from ttable (2,522).Greater from the relationship between the balance using conservative style at State Vocational High School 1 Cirebon, which has a moderate correlation, where by using the product moment formula calculation the value is 0.552> 0.374 and comes from a significant test, it turns out that count is larger than ttable (3.442 > 1.701), then H0 is rejected, it means that there is a significant correlation between the balance using Ortodok’s Style in Cirebon students.